Assessing Water Quality Index in Kani-Qirzhala Area, Erbil City, Kurdistan Region of Iraq - Noor Yashooa; Dana Mawlood; Varoujan Sissakian (Iraqi Geological Journal, 2024)
Groundwater is an essential water source in many areas in the Kurdistan Region of Iraq (KRI). The groundwater can be used for many purposes such as municipal, agricultural, and domestic. The objective of this study is to assess the quality of groundwater in the Kani-Qirzhala area. The study area covers 60 km2, and includes twenty-seven water wells, which have been selected and used to study the water quality parameters in such area. Canadian Council of Ministers for the Environment Water Quality Index method was used to evaluate Water Quality Index and SPSS software version 25 even to study the correlation between Water Quality Index and water quality parameters. The results indicated that the quality of water in most of the wells is fair, except the quality of water in wells 19, 24, and 27 is found to be poor. Well19 is located close to the Erbil landfill site (Kani-Qirzhala) and this poor quality is due to the effect of Landfill site leachate. The Well 24 is in the Erbil store area where the leachate of landfill is discharged to this surrounding area. The quality of water in well 27, on the other hand, was marginal and existed on the eastern side of the study area. The significant correlation revealed a good correlation between WQI and water quality parameters such as (pH, EC, TDS, Ca2+ Na1+, Mg2+, NO3-1, K1+, SO42-, Cl1-, Hardness, Alkalinity, Iron, and Copper).